Analysis of The Causes of Delays and Overbudget And Mitigation To Overcome Them In PT.WER Construction Projects - Imam Faizal Rosyidin; Ridho Bayuaji (Jurnal Indonesia Sosial Teknologi, 2024)
This study discusses variables that affect delays and overbudget in construction projects at PT. WER. Taking the approach of multiple linear regression analysis and the Relative Important Index (RII), this study shows that the most influential variables for delay and overbudget involve unavailability of manpower, changes in the behavior of the surrounding community, lack of project team knowledge about work sites, lack of knowledge transfer between project teams, and lack of maturity of project team competencies. The results of the study provide an in-depth understanding of the condition of PT. WER, which at certain periods experienced delays and overbudgets on a number of its projects. The proposed mitigation measures involve partnerships with educational institutions to increase the availability of skilled labor, improve communication with local communities, increase project team knowledge through training and guidance, encourage knowledge transfer between project teams, and implement continuous training programs to improve project team competencies. The conclusion of this study provides a foundation for companies to develop more effective mitigation strategies to achieve optimal project success.